1976
DOI: 10.1038/ki.1976.126
|View full text |Cite
|
Sign up to set email alerts
|

Factors in the dialysis regimen which contribute to alterations in the abnormalities of uremia

Abstract: While hemodialysis therapy in its present form is capable of sustaining life, dialysis patients are not metabolically normal and we are unable to say what technical factors contribute adequate therapy. Recent efforts to resolve these problems have led to the assumption that substances in the molecular weight range of 800 to 3000 daltons may be pathogenic in uremia and these may not be effectively removed by dialysis. Accordingly, four groups of patients (ten each) underwent changes in their routine which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…the tubularly secreted 'organic acid-like' com pounds [8,16], which have been shown to be toxic in in vitro experiments at concentrations found in uremic se rum. Further kinetic studies and clinical investigation of their toxicity might improve the definition o f 'adequate dialysis' [8,16,25,[35][36][37][38][39], Furthermore, the present study describes the dialysis-induced alteration of bound and nonbound fractions of accumulating solutes that are partly bound to protein (e.g. hippuric acid and indoxyl sulfate) and which have been reported to inhibit protein binding of drugs in sera of renal patients [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the tubularly secreted 'organic acid-like' com pounds [8,16], which have been shown to be toxic in in vitro experiments at concentrations found in uremic se rum. Further kinetic studies and clinical investigation of their toxicity might improve the definition o f 'adequate dialysis' [8,16,25,[35][36][37][38][39], Furthermore, the present study describes the dialysis-induced alteration of bound and nonbound fractions of accumulating solutes that are partly bound to protein (e.g. hippuric acid and indoxyl sulfate) and which have been reported to inhibit protein binding of drugs in sera of renal patients [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…A more quanti tative approach requires accurate knowledge of other factors that determine solute blood levels in dialyzed patients, e.g. hemoconcentration, compartmentalization and solute generation rate [11,25]. Only few such data area available.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiol ogy of uremic neuropathy has not yet been completely clarified, the most frequent as sumption is that accumulation of uremic toxins is the main factor causing peripheral nerve damage. Even though some studies documented that the degree of neuropathy is not related with dialysis index [2] and that inadequate dialysis treatment does not nec essarily worsen nerve conduction velocities [21], there is evidence that uremic polyneu ropathy is related with the retention of either middle [12,13,22] or small molecule [23] toxins. MNCV was higher in HD patients with vitamin BJ2 clearance greater than 30 liters per week than in those with a lower clearance [23], The improvement of uremic neuropathy was achieved in HD patients in creasing dialysis removal of small [23] or middle molecules [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies documented that the degree of neuropathy is not related with dialysis index [2] and that inadequate dialysis treatment does not nec essarily worsen nerve conduction velocities [21], there is evidence that uremic polyneu ropathy is related with the retention of either middle [12,13,22] or small molecule [23] toxins. MNCV was higher in HD patients with vitamin BJ2 clearance greater than 30 liters per week than in those with a lower clearance [23], The improvement of uremic neuropathy was achieved in HD patients in creasing dialysis removal of small [23] or middle molecules [11][12][13]. Teshan et al [7], evaluating the results of the National Coop erative Dialysis Study concerning the effects of different HD treatment regimens on electroneurophysiological parameters, showed that the deterioration of peripheral nerve indices was most marked in group IV (short dialysis time, high BUN) and less in group II (long dialysis time, high BUN) in compari son with the groups with lower BUN.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, urea enters from (net) protein catabolism as a zero order function, G. This process is considered zero order because it is generally constant over the time intervals represented by the period of dialysis treatment. A few investigators have suggested that urea generation may be other then zero order through feedback to dietary protein intake which may be a function of urea levels (30). It has also been shown that dialysis itself may be catabolic so that G may be a function of time, being greater during and immediately following dialysis and less immediately preceding dialysis (Borah, Gotch and Sargent et aI, unpublished work).…”
Section: Urea Entry Into the Systemmentioning
confidence: 97%